Jesus the purifier: John's gospel and the fourth quest for the historical jesus - Blomberg, Craig L. (Baker Academic, 2023)
Intro -- Half Title Page -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Abbreviations -- Introduction -- 1. The Original Quest for the Historical Jesus -- 2. No Quest and New Quest? -- 3. Launching the Third Quest with a Jewish Jesus -- 4. The Jesus Seminar and Its Kin: A Step Back in Time -- 5. Has the Third Quest Played Itself Out? -- 6. Foreshadowing the Fourth Quest: Rehabilitating the Gospel of John -- 7. Purification, Baptism, and Transformation in John 1-4 -- 8. Purification Starting to Change in John 5-11 -- 9. Ritual Purity Fades Away in John 12-21 -- 10. Purity and the Historical Jesus of the Synoptics -- Conclusion -- Index of Authors -- Index of Scripture and Other Ancient Writings -- Cover Flaps -- Back Cover.